FINANCIAL MARKET: CONTENT ANALYSIS OF THE FEATURES OF INTERPRETATION - Hariaha , Lesia (Socio-economic relations in the digital society, 2021)
Abstract. The genesis of approaches to the interpretation and functioning of the financial market is due to thedevelopment of the global post-industrial information society. Despite the accelerated pace of development of thefinancial market, the theoretical and methodological principles of its formation and operation are unsystematicand fragmentary, so they need additional justification.The content analysis of the peculiarities of the interpretation of the financial market is carried out. Scientificapproaches to the definition of the concept of «financial market» are systematized and content analysis of itsinterpretation is carried out. A sample of definitions of the concept of «financial market» was formed; thecomponent composition of the concept is highlighted; the number of mentions of each component is counted;the most representative components have been identified and ranked. The main components that shape theinterpretation of the concept of financial market are identified, namely: financial assets (instruments, resources),system (set) of relations, financial institutions (intermediaries), supply and demand (conditions), component(sphere) of the financial system and the component of the economy (economic space). The use of thesecomponents in the definitions of the financial market is characterized. An integrated definition of the financialmarket as a specific supporting area of the financial system, which is essentially a system of economic and legalrelations arising from the formation, use, circulation, transformation, distribution and redistribution of financialresources (embodied in financial assets); the market in which buyers and sellers of financial resources interact,where demand and supply for them is formed; a set of financial institutions that provide financial servicesthrough the appropriate infrastructure; a set of independent segments (credit, stock, currency, insurance, etc.),the operation of which should contribute to sustainable development and economic growth using traditionaland innovative financial instruments and technologies.Keywords: financial market, financial assets, financial institutions, supply and demand, content analysis.JEL Classification: G10, G20, О16Formulas: 0; fig.: 2; tabl.: 2; bibl.: 17.
Keywords: financial market; financial assets; financial institutions; supply and demand; content analysis